Meningkatkan Kesadaran Digital: Peran Literasi Digital Dalam Merespon Masalah Moral dan Ketimpangan Sosial Menuju Pencapaian SDGS 2030 - Rahma Nurul Adhani; Vivi Rahmawati; Ichsan Fauzi Rachman (CV. ALIM'SPUBLISHING, 2024)
Digital Literacy is a science that discusses digital media, such as communication tools, internet networks, and so on. Digital literacy plays an important role in helping individuals understand the risks associated with technology use and take appropriate action to protect themselves and their privacy. Morals are human life behavior, which is based on awareness that he is bound by the necessity to achieve good, in accordance with the values and norms that apply in his environment. Social inequality itself is a condition that exists in society which shows an imbalance due to differences in aspects that exist in society, both from an economic, social and cultural perspective. By increasing digital literacy in responding to moral problems and social inequality, this digital literacy plays a very important role, for everyone on this planet earth, in order to achieve the mission of sustainable development goals throughout the world, especially Indonesia. This research is a type of literature review research by looking for theoretical references that are relevant to the cases or problems found. In the increasingly developing digital era, digital awareness and digital literacy are important keys in overcoming moral challenges and social inequality. The discussion also discusses the relationship between digital literacy and moral issues, the relationship between digital literacy and social inequality, and the contribution of digital literacy to achieving SDGs 2030. So the result of everything is about how important digital literacy is in the current era and about the relationship between digital literacy and Moral problems and social inequality aim to improve the welfare of society so that it will be more advanced in the future.